Kondisi Optimum Adsorpsi Arang Hayati dari Kulit Pisang Raja (Musa X paradisiaca L.) terhadap Logam Timbal (Pb) dan Tembaga (Cu) - Tanggebono, Iren S. A.; Tiwow, Vanny M. A.; Jura, Minarni Rama (Jurnal Akademika Kimia, 2018)
This study aimed to determine the optimum condition of biocharcoal from banana peel on adsorption of lead (Pb) and copper (Cu) metals based on the variation of weights and biocharcoal contact times. Banana peel used in this research were taken from Sidondo III the village, Sigi, Central Sulawesi. To determine absorbed metals in biocharcoal banana peel was measured by a spectrophotometer spectroDirect. The results showed that the optimum weight of adsorption lead (Pb) ion was 80 mg and copper (Cu) ion was 40 mg with each percentage adsorption of 73.91% and 21.23%, respectively. The optimum time to adsorb lead and copper ions was 90 minutes with the percentage adsorption of 89.13% for lead ion and 25.86% for copper ion.